Gender-Related Differential Item Functioning of 2015 Wassce Core Mathematics Results in Southern Ghana Using Logistic Regression Procedure - Brew, Ruth Annan; Cobbinah, Andrews (European Scientific Journal, ESJ, 2020)
Differential item functioning (DIF) occurs when individuals of the same ability level from separate groups have a different probability of answering an item correctly. This study was conducted in two parts: in the first part a real 2015 West African Senior Secondary Certificate Examination (WASSCE) core mathematics test data were analyzed for uniform and nonuniform DIF using binary logistic regression (LR) procedure and in the second part, content analysis of items identified as DIF were classified under the levels of the cognitive domain by experts. Three research questions were formulated for the study. A sample of 4,285 male and 3,712 female candidates were selected from a population of 15,258 candidates who sat for the examination in 2015 from 20 selected schools in Southern Ghana. The instrument for the study was the 50 multiple-choice core mathematics items. The findings showed that there was 43 significant gender differential item functioning items of which 9 were uniform and 34 non-uniform. Also, the content analysis revealed that items that favoured males were mainly number and numeration, algebraic processes, probability and statistics and mensuration whiles plane geometry and coordinate geometry revealed DIF in favour of females. It was concluded that test items used were not free from gender DIF. It was recommended that DIF studies should be conducted by test developers in order to be review or exclude DIF items to enhance fairness in assessment.